2021
DOI: 10.15586/ijfs.v33i2.2012
|View full text |Cite
|
Sign up to set email alerts
|

Composition and nutritional evaluation of amino acids in Mimai Qu rice wine

Abstract: An amino acid analyzer was used to detect free amino acids (FAA) in Mimai Qu rice wines (SMW and DMW) and control wine samples (Chinese rice wine [CRW] and Japanese sake [JNS]). It was found that CRW had the highest total amino acid (TAA) content (~2814 mg/L), followed by SMW (~2509 mg/L) and DMW (~1474 mg/L), while JNS had the least (~917 mg/L). Amino acid ratio coefficient method (SRCAA), linear regression method, cluster analysis (CA) and principal component analysis (PCA) were used for evaluating the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Salinity has an impact on the fatty acid composition by altering the physiological metabolic pathways in aquatic animals, potentially related to providing energy for osmotic regulation [9,42]. Te content of polyunsaturated fatty acids (PUFA) is refective of the nutritional value of aquatic products, particularly long-chain polyunsaturated fatty acids (LC-PUFA), which are considered essential fatty acids (EFA) for organism development and growth [43]. Cheng et al [7] reported that the muscle PUFA content of Nile tilapia fed under 12 ppt salinity for 56 days was signifcantly higher than that of freshwater.…”
Section: Efect Of Salinity On the Content Of Fatty Acid Of O Aureusmentioning
confidence: 99%
“…Salinity has an impact on the fatty acid composition by altering the physiological metabolic pathways in aquatic animals, potentially related to providing energy for osmotic regulation [9,42]. Te content of polyunsaturated fatty acids (PUFA) is refective of the nutritional value of aquatic products, particularly long-chain polyunsaturated fatty acids (LC-PUFA), which are considered essential fatty acids (EFA) for organism development and growth [43]. Cheng et al [7] reported that the muscle PUFA content of Nile tilapia fed under 12 ppt salinity for 56 days was signifcantly higher than that of freshwater.…”
Section: Efect Of Salinity On the Content Of Fatty Acid Of O Aureusmentioning
confidence: 99%
“…According to the pattern spectrum of essential amino acids proposed by the World Health Orgnization (WHO)/Food and Agriculture Organization (FAO), 20,21 the amino acid score (AAS) and the essential amino acid index (EAAI) were calculated. The pattern spectrum of essential amino acids is shown in Table S1.…”
Section: Analysis Of Protein Nutritional Valuementioning
confidence: 99%